2012
DOI: 10.4028/www.scientific.net/kem.520.187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Analysis of Distortion of Complex Shaped Ti-6Al-4V Compacts by Metal Injection Molding Process

Abstract: Titanium and its alloys have been widely used for medical and aerospace applications because of their excellent attributes of high specific strength, corrosion resistance, and biocompatibility. However, it is not easy to produce the complex shaped parts due to their poor castability and machinability. Metal injection molding (MIM) is one of suitable processing technique to produce the complex shaped parts in order to reduce the manufacturing cost. In this study, complex shaped Ti-6Al-4V compacts was prepared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The strength of the material is 450 MPa (65 ksi), with variations depending on composition and temperature. The material used for the implant component is Titanium base alloy Ti CP grade 2 [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strength of the material is 450 MPa (65 ksi), with variations depending on composition and temperature. The material used for the implant component is Titanium base alloy Ti CP grade 2 [15].…”
Section: Methodsmentioning
confidence: 99%
“…Diverse in metal powder sizes will cause an impact on the homogeneous and solidity of the feedstock when injected. Binder as an additive to metal powders consists of polymer, wax and additive agent [15,16].…”
Section: Methodsmentioning
confidence: 99%
“…While Ti64 is extensively used in the aerospace industry, the high quality standards required for application of any component in aerospace, means the MIM process faces significant hurdles before it can be accepted by this industry. Nonetheless, research has demonstrated that it is possible for the MIM process to manufacture Ti64 components with superior mechanical properties close to the ASTM standard range [5,43,51,100,101] especially by small addition of other elements such as B [43,45], C [71], Gd [58] and TiC [81]. However, most research work on MIM of Ti64 alloy has been specifically designed for biomedical applications [43,83,102] rather than other applications such as aerospace.…”
Section: Figure 6 Microstructure Of Mim Proceed Cp-ti Samples From Amentioning
confidence: 99%
“…ability to manufacture complex parts and rapid production) to manufacture small-to-medium sized intricate components and is particularly suited to mass production [4]. The process offers significant design freedom in shape complexity but most MIM parts are restricted to smaller than about 100 mm in size for high dimensional accuracy and consistency [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of the large sized parts, it becomes difficult to control the distortion and cracking because of the remained binder in the thick part and the large shrinkage during debinding and sintering process 2,3) . These defects were affected by gravity, friction and inhomogeneity of green density [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%